Alveolar cell composition in interstitial lung disease and the development of a pulmonary progressive fibrosing phenotype: a retrospective cohort study - Iris A. Simons; Bart G. Boerrigter; Maud C.M. Hovestadt; Kirsten A. Mooij-Kalverda; Shiqi Zhang; Leonoor S. Boers; Anke H. Maitland– van der Zee; Esther J. Nossent; Jan Willem Duitman (Respiratory Research)
Abstract Background Immunological bronchoalveolar lavage (iBAL) is a frequently employed diagnostic tool in interstitial lung disease (ILD). The association between iBAL cellular composition and disease progression remains elusive. We evaluated whether the alveolar cellular composition at initial diagnosis is predictive of the development of progressive pulmonary fibrosis (PPF) in patients with ILD. Methods A retrospective analysis of 111 patients diagnosed with ILD who underwent iBAL for diagnostic purposes between January 2018 and January 2023 was conducted. The identification of PPF was based on the criteria outlined in the ATS/ERS/JRS/ALAT clinical practice guidelines. Clinical data, pulmonary function tests, radiological imaging, and BAL cellular composition were collected. Groups were compared using the non-parametric Wilcoxon rank sum test. Linear mixed-effect modelling was used to assess the association between baseline cell composition and longitudinal lung function decline. Results A total of 33.3% of patients exhibited a PPF phenotype. A significant association between baseline iBAL CD4 + and CD8 + T cell percentages and forced vital capacity (FVC) decline within the first year was observed. Other cell types were not associated with ILD progression within one-year of follow-up. Conclusions CD4 + and CD8 + T cell percentages significantly correlated with FVC changes in patients with fibrotic ILD. No further associations were found between the baseline iBAL cellular profiles and disease progression. These findings suggest that baseline iBAL cellular profiles may hold some promise in predicting fibrotic ILD disease progression. Further (prospective) studies using larger cohorts may be needed to elucidate the association between the cellular composition of iBAL fluid and pulmonary fibrosis progression.